Air‐Stable Cesium Lead Iodide Perovskite for Ultra‐Low Operating Voltage Resistive Switching. (20th December 2017) - Han, Ji Su; Le, Quyet Van; Choi, Jaeho; Hong, Kootak; Moon, Cheon Woo; Kim, Taemin Ludvic; Kim, Hyojung; Kim, Soo Young; Jang, Ho Won
Abstract: CsPbX3 (X = halide, Cl, Br, or I) all‐inorganic halide perovskites (IHPs) are regarded as promising functional materials because of their tunable optoelectronic characteristics and superior stability to organic–inorganic hybrid halide perovskites. Herein, nonvolatile resistive switching (RS) memory devices based on all‐inorganic CsPbI3 perovskite are reported. An air‐stable CsPbI3 perovskite film with a thickness of only 200 nm is successfully synthesized on a platinum‐coated silicon substrate using low temperature all‐solution process. The RS memory devices of Ag/polymethylmethacrylate (PMMA)/CsPbI3 /Pt/Ti/SiO2 /Si structure exhibit reproducible and reliable bipolar switching characteristics with an ultralow operating voltage (<+0.2 V), high on/off ratio (>10 6 ), reversible RS by pulse voltage operation (pulse duration < 1 ms), and multilevel data storage. The mechanical flexibility of the CsPbI3 perovskite RS memory device on a flexible substrate is also successfully confirmed. With analyzing the influence of phase transition in CsPbI3 on RS characteristics, a mechanism involving conducting filaments formed by metal cation migration is proposed to explain the RS behavior of the memory device. This study will contribute to the understanding of the intrinsic characteristics of IHPs for low‐voltage resistive switching and demonstrate the huge potential of them for use in low‐power consumption nonvolatile memory devices on next‐generation computing systems. Abstract : Cesium lead iodide (CsPbI3 ) perovskite, which is all‐inorganic halide perovskite, is synthesized on platinum‐coated silicon substrate for ultralow operating voltage resistive switching memory device. With analyzing the influence of phase transition in CsPbI3 on resistive switching characteristics, an electrochemical metallization mechanism involving metal conducting filaments is proposed to explain the resistive switching behavior for data storage.